2023
DOI: 10.1055/s-0043-1764491
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography–Guided Spinal Biopsy in Suspected Infective Spondylodiscitis: An Institutional Review of Its Utility

Abstract: Background Infectious spondylodiscitis is a debilitating condition and evidence-based medicine dictates confirming the diagnosis before treatment. Computed tomography–guided spinal biopsy plays a major role and hence we would like to determine its utility in current clinical practice. Purpose The purpose of this study is to determine the percentage of confirmatory positives of CT-guided spinal biopsy in patients who were clinicoradiologically diagnosed with infectious spondylitis. Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Usually, pyogenic infection is considered when acute neutrophilic infiltration is noted with widespread necrosis. Tuberculous vertebral infection is evoked when granuloma or caseous necrosis with chronic inflammation is noted, whereas it is considered as definitive when acid-fast bacillus bacteria is positive [ 99 ]. Many studies have shown the superiority of cytopathology over microbiological investigations in establishing the diagnostic of PSI [ 100 ], since it was demonstrated that histology could provide the diagnostic even when no specific infectious agent was isolated [ [63] , [80] , [99] , [100] , [101] ].…”
Section: Histopathological Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, pyogenic infection is considered when acute neutrophilic infiltration is noted with widespread necrosis. Tuberculous vertebral infection is evoked when granuloma or caseous necrosis with chronic inflammation is noted, whereas it is considered as definitive when acid-fast bacillus bacteria is positive [ 99 ]. Many studies have shown the superiority of cytopathology over microbiological investigations in establishing the diagnostic of PSI [ 100 ], since it was demonstrated that histology could provide the diagnostic even when no specific infectious agent was isolated [ [63] , [80] , [99] , [100] , [101] ].…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…Tuberculous vertebral infection is evoked when granuloma or caseous necrosis with chronic inflammation is noted, whereas it is considered as definitive when acid-fast bacillus bacteria is positive [ 99 ]. Many studies have shown the superiority of cytopathology over microbiological investigations in establishing the diagnostic of PSI [ 100 ], since it was demonstrated that histology could provide the diagnostic even when no specific infectious agent was isolated [ [63] , [80] , [99] , [100] , [101] ]. Two papers reported of a sensitivity ranging between 81% and 91%, and a specificity of 100% for histologic examinations [ [100] , [101] ].…”
Section: Histopathological Assessmentmentioning
confidence: 99%
“…We have read with interest the article by Ravichandran et al published in your highly valued journal, which evaluated the rate of positive computed tomography (CT)-assisted biopsy results in a large number of patients with clinically and radiologically suspected spondylodiscitis. 1 Such a study is valuable because the diagnosis is definitive when the causative organism is isolated, probable when at least one of the blood tests is consistent with the disease, and presumptive—if the typical CT and magnetic resonance imaging (MRI) features of the disease are present in the absence of any positive microbiological cultures. 2 Currently, CT-assisted biopsy is a recognized diagnostic tool that can provide isolation of the infectious pathogen, thus, allowing the initiation of adequate antibiotic therapy alone or after surgical intervention.…”
mentioning
confidence: 99%
“…We cannot agree with the treatment algorithm proposed by Ravichandran et al who suggested initiation of antibiotic therapy on a regular basis and only in case of conservative treatment failure to perform surgical intervention. 1 Recently, with the advances in the pharmaceutical industry, there is widely accepted view that conservative therapy can and should be applied in cases where there is no neurological deficit, spinal deformity, and segment instability. 4 …”
mentioning
confidence: 99%
See 1 more Smart Citation